An Algorithm for Reduction of Extracted Power from Photovoltaic Strings in Grid-Tied Photovoltaic Power Plants during Voltage Sags - Tafti, Hossein Dehghani (2016)
Due to the high penetration of the installed distributed generation units in the power system, the injection of reactive power is required for the medium-scale and large-scale grid-connected photovoltaic power plants (PVPPs). Because of the current limitation of the grid-connected inverter, the injected active power should be reduced during voltage sags. In order to obtain a constant dc-link voltage in a multi-string PVPP, the extracted power from PV strings should be equal to the injected power to the grid in all operating conditions (excluding power losses). Therefore, the extracted power of PV strings should be reduced during voltage sags. In this paper, an algorithm is proposed for determining the reference voltage of the PV string which results in a reduction of the output power to a certain amount. The proposed algorithm calculates the reference voltage for the dc/dc converter controller, based on the characteristics of the power-voltage curve of the PV string and therefore, no modification is required in the the controller of the dc/dc converter. Simulation results on a 50-kW PV string verified the effectiveness of the proposed algorithm in reducing the power from PV strings under different irradiation and reference power values.